The Value of Tasawuf as a Basis of Religious Moderation Education - Budiono, Budiono (Jurnal Paradigma, 2024)
The term "moderation" is often associated with the attitude of mediating a problem. In the Big Indonesian Dictionary, the word "moderation" is defined as "reduction of violence" or "avoidance of extremes". In general, the term moderation is often understood as the activity of guiding, directing and mediating interactive communication that occurs between several parties in oral and written form. In other words, moderation is an action or attitude that is able to mediate (washith) in an effort to resolve problems between two or more parties, so that the problem finds a solution and peace by reducing the potential for violence or extremes. Keyword : moderation, mediate (washith), solution.